2008
DOI: 10.1016/j.vetmic.2007.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Chicken lung lectin is a functional C-type lectin and inhibits haemagglutination by influenza A virus

Abstract: Many proteins of the calcium-dependent (C-type) lectin family have been shown to play an important role in innate immunity. They can bind to a broad range of carbohydrates, which enables them to interact with ligands present on the surface of micro-organisms. We previously reported the finding of a new putative chicken lectin, which was predominantly localized to the respiratory tract, and thus termed chicken lung lectin (cLL). In order to investigate the biochemical and biophysical properties of cLL, the reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Molecules involved in innate immunity to pathogens, such as CLL1, PTX3 and GAL4, were only upregulated in L1. C-type lectins and PTX3 are known to have antiviral activity against influenza virus (Hogenkamp et al, 2008;Reading et al, 2008). In mice, b-defensins such as GAL4 are upregulated in the airway epithelial cells due to influenza virus infection (Chong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Molecules involved in innate immunity to pathogens, such as CLL1, PTX3 and GAL4, were only upregulated in L1. C-type lectins and PTX3 are known to have antiviral activity against influenza virus (Hogenkamp et al, 2008;Reading et al, 2008). In mice, b-defensins such as GAL4 are upregulated in the airway epithelial cells due to influenza virus infection (Chong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, the collagen-like domain is not needed for trimerization of collectins, and hence a trimer could be the active form of cLL. Chemical cross-linking experiments have indeed shown that recombinant cLL in solution is oligomerized, although the exact number of monomers involved was not determined (Hogenkamp et al, 2008). The role of the collagen domain of mammalian SP-A has not been completely elucidated but it seems to be involved in stabilization of the protein and may act as a spacer to facilitate interactions between different phospholipid structures, for example, in tubular myelin and for agglutination of microbes (Palaniyar et al, 2001).…”
Section: The Role Of Avian Collectins In Host Defence (Eja Veldmentioning
confidence: 99%
“…Interestingly within 24 h a downregulation was observed in lung tissue, while collectins were generally upregulated in trachea, indicating differential expression depending on the location within the respiratory tract (Reemers et al, 2009). In addition, recombinantly expressed cLL showed viral hemagglutination inhibition activity in vitro (Hogenkamp et al, 2008). These first results on avian collectins indicate that they could be important in innate defence of the chicken lung against (viral) infections.…”
Section: The Role Of Avian Collectins In Host Defence (Eja Veldmentioning
confidence: 99%
“…In addition, a chicken lung lectin (cLL) with high sequence homology to cSP-A was reported. Whether chicken collectins can protect against influenza A virus inoculation has not been clarified, but cLL has been shown to possess in vitro hemagglutination inhibiting activity (Hogenkamp et al, 2008). Avian influenza virus (AIV) enters the respiratory epithelium using sialic acid receptors linked to galactose by an a-2,3 linkage, although the pattern of receptor distribution in chickens is less defined than in mammals (Wan and Perez, 2006).…”
Section: Introductionmentioning
confidence: 99%